APPLICATION OF BIOFLOC TECHNOLOGY IN REARING RED TILAPIA (Oreochromis niloticus) AT DIFFERENT STOCKING DENSITIES IN BRACKISH WATER - Ningsih, Kurnia; Putra, Iskandar; Pamukas, Niken Ayu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Red tilapia is a fish with a relatively wide tolerance to salinity (euryhaline) changes, making it possible to cultivate red tilapia in brackish waters. Additionally, intensive farming environments can support increased stocking density. The application of biofloc technology can help address this issue. Biofloc technology is an alternative approach to addressing water quality issues in water bodies, adapted from conventional domestic wastewater treatment techniques, and can also serve as a source of natural food. This research aimed to determine the best stocking density of red tilapia reared in brackish water using biofloc technology. The method used in this research is the experimental method of Completely Randomized Design (CRD) with one factor, five levels of treatment, and three replicates. The treatments applied were 20 fish/80 L (P1), 30 fish/80 L (P2), 40 fish/80 L (P3), 50 fish/80 L (P4) and 60 fish/80 L (P5). The red tilapia used as test fish were 3-5 cm in size and adapted to 17 ppt salinity. Feed with commercial pellets 3 times a day in sufficient amounts. This research was conducted for 50 days. The results showed the best stocking density was obtained in P4 (50 fish/80 L) which produced absolute weight of 8,87 ± 0,12 g, absolute length of 3,57 ± 0,07 cm, specific growth rate of 3,55 ± 0,12%, feed conversion ratio of 0,83 ± 0,06 kg, feed efficiency of 120,32 ± 7,81%, survival rate of 86 ± 4% and blood glucose level of 71 ± 5,13 mg/dL.